BIOLOGY AND IMPORTANCE OF PROMISING MEDICINAL PLANTS USED IN THE FOOD INDUSTRY (Multidisciplinary Journal of Science and Technology, 2026)
This article discusses promising medicinal plants used in the food industry, their biologically active substances and their importance in the production of functional products. The issues of using medicinal plants as natural additives, antioxidants, preservatives and biologically active components are analyzed. Plants play a key role in the survival and livelihood of humans and animals. Because they are natural sources of food, fodder, medicine, clothing, air, and many other substances. It is known that plants store various organic substances, their compounds, and mineral salts necessary for life in one or another of their organs. For this reason, humans have been using various organs of plants for various purposes.They are not limited to cultivated plant species and varieties, but have been learning and studying the inner secrets of wild plant species growing around them and using them for many years.